5G IoT and edge computing for smart healthcare - Bhoi, Akash Kumar (Academic Press, 2022)
5G IoT and Edge Computing for Smart Healthcare addresses the importance of a 5G IoT and Edge-Cognitive-Computing-based system for the successful implementation and realization of a smart-healthcare system. The book provides insights on 5G technologies, along with intelligent processing algorithms/processors that have been adopted for processing the medical data that would assist in addressing the challenges in computer-aided diagnosis and clinical risk analysis on a real-time basis. Each chapter is self-sufficient, solving real-time problems through novel approaches that help the audience acquire the right knowledge. With the progressive development of medical and communication - computer technologies, the healthcare system has seen a tremendous opportunity to support the demand of today's new requirements. Focuses on the advancement of 5G in terms of its security and privacy aspects, which is very important in health care systems Address advancements in signal processing and, more specifically, the cognitive computing algorithm to make the system more real-time Gives insights into various information-processing models and the architecture of layers to realize a 5G based smart health care system.
Keywords: Medical informatics; Artificial intelligence -- Medical applications; 5G mobile communication systems; Edge computing; Internet of things; Médecine; Informatique; Intelligence artificielle en médecine; Communications mobiles 5G; Internet des objets; Artificial intelligence; Medical applications